Mangosteen (Garcinia mangostana): extraction, purification, bioactivities and toxicities - Zamarudin, Zalikha; Bin Abdullah Sani, Muhamad Shirwan; Nordin, Noor Faizul Hadry; Amid, Azura; Mohd Hashim, Amalia (IIUM Press, 2023)
Mangosteen (Garcinia mangostana) is a popular tropical fruit known as ‘the queen of fruits’ due to its delicious flavour. It comprises phytochemicals, flavonoids, and polyphenols such as xanthones, anthocyanins, and phenolic acids. The G. mangostana pericarp, seed, and flesh bioactive compounds have been shown to have anticancer, antitumor, wound healing, anti- inflammatory, antigenotoxic, antioxidative, antimicrobial, and antiviral properties. This review focuses on the bioactivity of G. mangostana, with the most common bioactive compound discovered being xanthone, which is frequently used in cosmetics, antimicrobials, antioxidants, and pharmaceutical research. Various extraction methods, both conventional and non- conventional, have been used in studies, depending on the goal of the research. This review concludes by using a computerised database search technique to discuss the extraction methods available and the properties of the bioactive compounds found in various parts of G. mangostana, including the pericarp, seed, and flesh.